2002
DOI: 10.1177/1096348002026002004
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Real Estate Investment Trusts' Risk Features and Beta Determinants

Abstract: This study examines the risk features of hotel real estate investment trust (REIT) firms. In particular, it investigates the systematic and unsystematic risk of hotel REIT stocks and the determinants of their systematic risk, or beta. Using the financial data of 19 U.S. hotel REIT firms from 1993 through 1999, the authors found that 84% of the firms'total risk was contributed by firm-specific, unsystematic risk. Systematic risk correlated positively with debt leverage and growth but negatively with firm size. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 27 publications
10
105
0
1
Order By: Relevance
“…Kim et al (2002), Lee and Jang (2007), Borde (1998), Gu and Kim (2002), and W. Kim et al (2007) found leverage as a key risk factor in explaining the performance of firms in the hotel, airline, and casino industries, respectively. In this article, we investigate the relation between leverage and stock returns of all hospitality firms listed in the London Stock Exchange with operations as hotels, restaurants, pubs, travel companies, and entertainment firms.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (2002), Lee and Jang (2007), Borde (1998), Gu and Kim (2002), and W. Kim et al (2007) found leverage as a key risk factor in explaining the performance of firms in the hotel, airline, and casino industries, respectively. In this article, we investigate the relation between leverage and stock returns of all hospitality firms listed in the London Stock Exchange with operations as hotels, restaurants, pubs, travel companies, and entertainment firms.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The Introduction Leverage is a key variable that plays an important role on firm performance (Delcoure & Dickens, 2004;Mandelker & Rhee, 1984). Borde (1998), Gu and Kim (2002), H. Kim, Gu, and Mattila (2002), W. Kim, Ryan, and Ceschini (2007), and Lee and Jang (2007) found that leverage is an important risk factor that affects hospitality firms in particular. Thus, we examine the relation between leverage and stock returns in the hospitality sector, which is a sector that is very reliant on external financing.…”
mentioning
confidence: 99%
“…Leverage keuangan berkaitan dengan sumber dana yang berasal dari utang yang akan mengakibatkan beban tetap tertentu dengan harapan akan meningkatkan keuntungan pemilik modal (Weston dan Brigham, 1991 Kim et al, (2002); Logue & Merville (1972;Melicher (1974). Perusahaan yang relatif besar cenderung terdiversifikasi dan tidak mudah mengalami kebangkrutan sertata risikonya rendah (Titman & Wessels, 1988).…”
Section: Pendahuluanunclassified
“…For REITs in the hotel, storage, and office categories, the reported returns and risk are higher than those of the S&P's MidCap Index. Kim et al (2002b) investigate the risk features of hotel REITs in terms of systematic and unsystematic risk components. The findings show that 84% of the total risk of hotel REITs is attributed to unsystematic risk and that the systematic risk is shown to be positively correlated withdebt ratio and asset growth of hotel REITs but negatively with REIT's size.…”
Section: Literature Reviewmentioning
confidence: 99%